TRENDS IN GLOBAL TRANSFORMATIONS OF COUNTRIES IN THE CONTEXT OF THEIR DEVELOPMENT AND ENSURING NATIONAL SECURITY - Olena A. Parshyna; Marharyta Yu. Parshyna; Tetiana V. Chumak; Ljudmila I. Yarmolenko (Academy Review)
World development at the current stage is accompanied by complex integration processes and global transformations. In recent years, there has been a steady trend of growing transnational threats and international conflicts, which has a negative impact on the key characteristics of states’ ability to ensure sustainable development in the face of worsening global security problems. The purpose of the article is to identify trends in the global transformations of countries in the context of their development and assurance of national security. Studies have been conducted on defining and quantifying the main characteristics of states, taking into account key aspects such as security and development. Methodological approaches to determining indices and indicators, based on multidimensional methods that enable a quantitative assessment of state weakness levels, have been considered. A scientific and methodological approach has been proposed, and research on a selected group of countries has been conducted to analyze the dynamics of their development and national security. This approach includes assessing the level of country weakness using the Fragile States Index and its component indicators and criteria. By utilizing the Fragile States Index from 2006 to 2023, it was possible to identify trends in state transformations in countries such as Afghanistan, the United Kingdom, Indonesia, Iran, China, the United States, and Ukraine. An analysis of global transformations in Ukraine has been conducted, distinguishing three periods based on this analysis: the first period from 2006 to 2014, the second from 2015 to 2020, and the third covering the last two years, during which the country has been engaged in armed conflict (2022–2023). The system of indicators and criteria within the Fragile States Index reveals a significant deterioration in 2023 compared to 2013. Mathematical models of changes in the Fragile States Index for China and Indonesia have been constructed, along with an assessment of their accuracy, enabling the forecasting of strengthening trends for these countries in future periods. The practical application of the proposed scientific and methodological approach allows for analytical processing that incorporates a multidimensional approach to assessing state weakness in the context of development trends and national security. Effective strategic decisions can be developed to enhance resilience amid global transformations, based on analytical information and identified gaps in the key characteristics of states.